Inglés Intermedio 1 - Montiel Lira, Diana Alicia (My University, 2002)
INDICE. 1.-CAPITULO UNO. 1.1 At the restaurant 1.2 Simple present 1.3 Question words 2.-CAPITULO DOS 2.1 Pollution 2.2 Nouns and adjectives 3.-CAPITULO TRES 3.1 Prevent fire 3.2 Present progressive 3.3 Affirmative 3.4 Negative 3.5 Interrogative
Keywords: Inglés intermedio 1; Order, please, of course, thank you, you´re welcome, waitress, simple present, affirmative, negative, I like, I don´t like, interrogative, pollution, nouns, adjectives, present progressive, present progressive affirmative, present progressive negative